Solitons in crystalline processes : statistical thermodynamics of structural phase transitions and mesoscopic disorder - Fujimoto, Minoru (IOP (Series). Release 4., 2017)
Solitons in Crystalline Processes is an introduction to the statistical thermodynamics of phase transitions in crystallized solids. This book is written as an introductory treatise with respect to the soliton concept, from structural transitions where the crystal symmetry changes, to magnets and superconductors, describing the role of nonlinear excitations in detail.